When fear leads towards preventive measures: A study of newspapers’ coverage and public perception on COVID-19 pandemic. - Saeed, Muzammil; Ali , Farahat; Nawaz , Nighat (Journal of Peace, Development and Communication, 2021)
This research intends to examine and analyze the coverage of COVID-19 pandemic in leading Urdu newspapers of Pakistan and its effects on readers. For this purpose, this study applied quantitative content analysis and survey method. News stories (n=690) of COVID-19 were selected randomly from two newspapers, daily Jang and daily Express to find out the elements of fear, hope, awareness and precautions, while news readers and viewers were selected as respondents (n=455) to know the fear level and preventive measures taken by the news audience. The results found that newspapers paid attention to the crisis in terms of risk perception, and public opted preventive measures after news exposure. Survey result shows that television viewers have greater fear of COVID-19 than the social media users and newspapers readers. It further shows that females have more fear of COVID-19 than males, and they are taking more precautionary measures. Moreover, result shows that fear of COVID-19 is a significant predictor of precautionary behaviour for males than females. Limitations and future directions are discussed in details.